Sistem Operasional Unit Pelayanan Terpadu Satu Atap (UPTSA) Sebagai Modal Pelayanan Sipil Dinas Perizinan Pemerintah Kota Yogyakarta - Baskoro Wicaksono (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
Prima Public Services are services that are under one roof agencies. In Yogyakarta, one-stop service is realized in the form of the establishment of the “Dinas Perizinan”, formerly known as One-Stop Integrated Service Unit (UPTSA). The existence of this new service brings change in The pattern of service so that it gets a good response from the public. This research was conducted in Yogyakarta is First, How the production and distribution of "public services" Licensing Agency of Yogyakarta as a One-Stop Integrated Service Unit (UPTSA). Secondly, How Public Service standard form used to get Excellent Service award at the National Level. Third, how the public response to the quality standards of public service in the Department of Licensing Yogyakarta. This study uses qualitative method with a phenomenological research strategy. Data collection techniques in this study using two ways, namely depth interview and review of secondary documents. The result Showed UPTSA changes to "Dinas Perizinan" had a positive impact on service delivery, which formerly slow, non-transparent and unaccountable and unfriendly bertransformarsi be fast, transparent, responsive, friendly and accountable. On the other hand the use of information technology is a major weapon to simplify, improve and speed up service. This makes people give a positive response and appreciation of the quality of public services in the field of licensing.